A "forma-tela" : modos de pensar a tela do cinema na arte contemporânea - Ferreira, Alana de Oliveira (2018)
The dissertation investigates the questions related to the use os th cinema screen in the spaces of contemporary art, how art deconstructs the normative screen of cinema to create new relation between the spectator and the screen-form within that environm